The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1182/blood.v106.11.4615.4615
|View full text |Cite
|
Sign up to set email alerts
|

Novel Therapeutic Approach Yields Excellent Results in Minimally Differentiated Acute Myeloid Leukemia (AML-M0): Time To Think out of the Box.

Abstract: Background: AML M0 has dismal complete remission (CR) rates (<50% in most series) and poor long term survival with conventional combination chemotherapy (CT). Thus it is considered a candidate for allogenic bone marrow transplantation (BMT) in first remission and also for other novel therapeutic approaches. There is increasing recognition of angiogenesis as a pathogenic and prognostic factor in AML. The objective of our study was to evaluate the efficacy of low-dose oral metronomic CT in patients with AML-M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…This regimen has been reported by the Tata Memorial Hospital, Mumbai, India 31,32 (G. Narula, personal communication). It includes a combination of oral etoposide, 6‐thioguanine (6‐TG), and prednisolone as follows: (a) etoposide at 50 mg/m 2 orally once a day for 21 days, if oral preparation is unavailable, replace with intravenous (i.v.)…”
Section: Treatment Guidelinesmentioning
confidence: 70%
See 3 more Smart Citations
“…This regimen has been reported by the Tata Memorial Hospital, Mumbai, India 31,32 (G. Narula, personal communication). It includes a combination of oral etoposide, 6‐thioguanine (6‐TG), and prednisolone as follows: (a) etoposide at 50 mg/m 2 orally once a day for 21 days, if oral preparation is unavailable, replace with intravenous (i.v.)…”
Section: Treatment Guidelinesmentioning
confidence: 70%
“…Patients in such settings may have increased TRM if standard chemotherapy is administered upfront. However, the evidence supporting a metronomic approach to upfront chemotherapy in children with AML is limited 31,32 . In addition, there is concern regarding the development of resistance to chemotherapeutic drugs with the administration of low‐dose chemotherapy.…”
Section: Treatment Guidelinesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the main mechanism of the regimen in treating hematologic malignancies including AML is assumed to be the inhibition of tumor angiogenesis (Padró et al, 2000). Few observational studies and one case report had revealed favorable survival outcome of using metronomic chemotherapy in AML patients (Banavali et al, 2005;Tandon et al, 2013;Kapoor et al, 2016). To our knowledge, this study is the first randomized controlled trial to directly examine the efficacy and safety outcomes of metronomic chemotherapy in unfit AML patients.…”
Section: Discussionmentioning
confidence: 92%